السياحة العربية وأهميتها في الطلب السياحي السوري (دراسة تحليلية للفترة 2000-2007) - محمود, حبيب; شوباصي, شعبان (Latakia University Journal - Economic and Legal Sciences Series, 2019)
تعتبر السياحة مورداً اقتصادياً هاماً في سورية، وتمثل القاطرة الرئيسة في الاقتصاد الخدمي، مما رفع من أهمية دورها التنموي اقتصادياً واجتماعياً، وبلغت مساهمتها 14.4% من الناتج المحلي الإجمالي عام 2007، ونظراً لما تمتلكه سورية من مقومات سياحية هامة فهي قادرة على استقطاب ملايين السياح سنوياً، والسوق العربية تعتبر أحد أهم مصادر الطلب السياحي في سورية. بناءً على ما تقدم جاء هذا البحث للتعريف بأهمية السياحة العربية في استقرار الحركة السياحية وتقدمها في سورية من خلال المؤشرات الإحصائية، وتضمن البحث مقارنة الطلب السياحي العربي مع باقي مصادر الطلب السياحي السوري، ودراسة تطور الطلب السياحي العربي في سورية وفقاً لمؤشرات عدد السياح، وعدد الليالي السياحية، وحجم الإنفاق السياحي العربي، كذلك يوضح البحث اختلاف خصائص الطلب السياحي العربي بين دولة عربية وأخرى، وبالتالي أهمية التمييز في عملية التسويق والترويج السياحي وفقاً للخصائص التي يتميز بها سياح كل دولة عربية، وكذلك معرفة الاستثمارات السياحية الأكثر طلباً للسياح العرب، والخدمات السياحية التي يفضلونها. Tourism is considered an important economic resource in Syria, and it represents the main engine in the economy of services. This raises the importance of its economic and social development role; its contribution reached 14.4% of the GDP in 2007. And since Syria possesses significant tourism potential, it is able to attract millions of tourists annually, and the Arab market is one of the most important resources of tourism demand in Syria. Depending on that, the research introduces the importance of Arab tourism in the stability and advancement of tourism movement in Syria through statistic indicators, and it includes a comparison of Arab tourism demand with the rest of the Syrian tourism demand resources, and a study of the development of the Arab tourism demand in Syria, according to indicators of number of tourists and tourism nights, and the size of the Arab tourism expenditure. It also shows differences of characteristics of Arab tourism demand among the Arab states, and thus the importance of distinction in the process of tourism marketing and promotion according to the characteristics that distinguish the tourists of every Arab state, and subsequently the importance of distinguishing the marketing and promotion processes according to the characteristics of tourists in each Arab stats as well as knowing the most demanding tourist investments for the Arab tourists, and the tourism services which they prefer.